2000
DOI: 10.1177/088626000015002003
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence

Abstract: To compare the severity of violence reported by women and men filing assault charges against an intimate partner, 100 complainants (90 women and 10 men) were interviewed. Measurement instruments included the Severity of Violence Against Women Scales, Danger Assessment Scale, Stalking Victimization Survey, and a quality of life index. Using independent t tests, no significant differences existed between male and female demographic characteristics. The majority of victims were African American, employed, and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…The findings of this study are consistent with another study that found women who experienced emotional abuse scored significantly lower for functional status than non‐abused women on seven of the eight subscales (Wagner & Mongan, 1998). Similarly, in another study, it was suggested that women who were victims of violence experienced adverse mental health, and decreased ability to function socially and emotionally, in addition to impaired physical performance, vitality, general health, and reports of bodily pain (McFarlane et al ., 2000). Bonomi et al .…”
Section: Discussionmentioning
confidence: 95%
“…The findings of this study are consistent with another study that found women who experienced emotional abuse scored significantly lower for functional status than non‐abused women on seven of the eight subscales (Wagner & Mongan, 1998). Similarly, in another study, it was suggested that women who were victims of violence experienced adverse mental health, and decreased ability to function socially and emotionally, in addition to impaired physical performance, vitality, general health, and reports of bodily pain (McFarlane et al ., 2000). Bonomi et al .…”
Section: Discussionmentioning
confidence: 95%
“…This can be regarded as emerging evidence for a gender symmetry in IPV reporting (McFarlane, Willson, Malacha, & Lemmey, 2000;Straus & Ramirez, 2007). This can be regarded as emerging evidence for a gender symmetry in IPV reporting (McFarlane, Willson, Malacha, & Lemmey, 2000;Straus & Ramirez, 2007).…”
Section: Gender Symmetry In the Reporting Of Ipvmentioning
confidence: 87%
“…Psychological victimization is even more prevalent than physical victimization, with one study finding that 90% of college women reported psychological victimization at some point in their relationships (Katz, Arias, & Beach, 2000). Several studies have demonstrated negative mental and physical health consequences of dating violence among women (Carlson, McNutt, Choi, & Rose, 2002;Coker et al, 2002;Golding, 1999;Kaura & Lohman, 2007;Lown & Vega, 2001), and a smaller literature has shown that men also suffer from negative mental health effects of dating violence (Dye & Eckhardt, 2000;McFarlane, Willson, Malecha, & Lemmey, 2000). This study focused on one specific correlate of dating violence victimization-anger-and examined potential differences in anger profiles across male and female undergraduates.…”
mentioning
confidence: 94%